New approach for propagated light with optical solitons by optical fiber in pseudohyperbolic space H02 - İnç, Mustafa; Korpinar, Talat; Korpinar, Zeliha; Baleanu, Dumitru; Cem Demirkol, Ridvan (Wiley, 2023)
In this paper, a new evolution of polarized light ray by optical fiber in the pseudohyperbolic space H-0(2) is examined. Firstly, the characterization of the parallel transportation law associated with the geometric pseudohyperbolic phase of the light ray is given. Later, a principle nature of electric and magnetic field along with the light ray in the pseudohyperbolic space H-0(2) is defined by the geometric invariants. Finally, optical solutions of nonlinear pseudohyperbolic Schrodinger's equations governing the propagation of electromagnetic fields are successfully derived by using the traveling wave hypothesis approach.
Keywords: geometric pseudohyperbolic phase; optical fiber; transformation equations; traveling wave hypothesis